2021
DOI: 10.1002/pmrj.12658
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic prevalence of ulnar nerve displacement at the elbow in young baseball players

Abstract: Background Overhead‐throwing athletes are at risk of elbow injury because of valgus stress, leading to unstable ulnar nerves and neuropathy. Studies regarding ulnar nerve damage/displacement have been performed primarily in adults. Objective To determine the prevalence and related factors associated with ulnar nerve displacement at the elbow in young baseball players. Design Cross‐sectional study. Participants Youth baseball players ages 10–12 years were eligible to participate. Exclusion criteria were history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Diagnostic ultrasound is also very helpful to identify nerve displacement on dynamic imaging with elbow flexion. More recently, Kawabata and colleagues found ultrasound evidence of dynamic ulnar nerve displacement in one third of asymptomatic youth baseball players examined 96 . Diagnostic ultrasound is also helpful in identifying morphological nerve abnormalities, such as increases in nerve cross sectional area 30 .…”
Section: Peripheral Neuropathies In Throwing Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic ultrasound is also very helpful to identify nerve displacement on dynamic imaging with elbow flexion. More recently, Kawabata and colleagues found ultrasound evidence of dynamic ulnar nerve displacement in one third of asymptomatic youth baseball players examined 96 . Diagnostic ultrasound is also helpful in identifying morphological nerve abnormalities, such as increases in nerve cross sectional area 30 .…”
Section: Peripheral Neuropathies In Throwing Athletesmentioning
confidence: 99%
“…More recently, Kawabata and colleagues found ultrasound evidence of dynamic ulnar nerve displacement in one third of asymptomatic youth baseball players examined. 96 Diagnostic ultrasound is also helpful in identifying morphological nerve abnormalities, such as increases in nerve cross sectional area. 30 MRI is not routinely used for the evaluation of ulnar neuropathy.…”
Section: Ulnar Nervementioning
confidence: 99%
“…Dynamic ultrasound can reveal the snapping of the ulnar nerve during elbow movements (44). A recent study using dynamic ultrasound visualization identified a significant prevalence of ulnar nerve displacement in young baseball players, although some forms of nerve subluxation may also be observed in asymptomatic patients (45). In case of ulnar neuropathy, nerve conduction studies and electromyography (EMG) can assess nerve damage but are not useful to identify the underlying aetiology.…”
Section: Extra-articular (Medial) Snappingmentioning
confidence: 99%
“…Imaging studies have been used to determine the effect of valgus torque on the medial elbow relative to ulnar nerve subluxation and neuropathy. While studies regarding ulnar nerve damage/displacement have been performed primarily in adults, a study by Kawabata et al (26) examined a group of 57 youth baseball players age 10 to 12 years, 31.6% identifying sonographic findings of ulnar nerve displacement correlating more commonly with the dominant hand and with tenderness to palpation of the arcade of Struther’s. With these findings in mind diagnostic ultrasound may be a valuable tool in identifying risk for injury in the throwing population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies have looked at factors related to injury in the youth baseball population over the past year ranging in topics from; early sport specialization (ESS) (12)(13)(14)(15)(16), pitch counts (17)(18)(19)(20)(21)(22)(23), prethrowing protocols (24,25), imaging findings (26), to body region-specific inquiries (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) in search for opportunities to reduce the risk of injury in this population. We will review a wide range of articles and their relevance to injury risk in this population.…”
Section: Literature Reviewmentioning
confidence: 99%